Evaluación y comparación de la microfiltración apical entre dos cementos biocerámicos BIO-C®-SEALER, Endoseal MTA in vitro. (2021)
The importance of sealing cements and their uses has evolved over the years. In a sealant material, it must be taken into account that it has good mechanical properties, low solubility, biocompatibility and, above all, that it contributes to the success of endodontic treatment